R1A SUBCLADES AND BRONZE AGE MIGRATIONS ON THE EURASIAN STEPPES - Horvath, Csaba Barnabas (European Scientific Journal, ESJ, 2016)
Until recently, our knowledge of the prehistoric world has been blur in many aspects. It was unclear, whether if migrations, conquest, or merely cultural diffusion led from one culture to the other. By the beginning of the 20th century, the introduction of genetics into the study of ancient history gave opportunity for a deeper insight to the prehistoric world. As more and more genetic traces are explored, it becomes more and more possible to identify the routes and time of prehistoric migrations. If we can decode the information hidden in genetic data, a turbulent picture of migrations and conquest between certain prehistoric cultures emerges in front of our eyes. This paper attempts to identify prehistoric migrations in Eastern Europe and Central Asia from the Neolithic to the Bronz Age, based on statistical data of genetic samples.